Education quality: applications to the higher education world - Marcos Recio, Juan Carlos (2014)
Humans are increasingly aware of the importance of building a society based on the improvement of education. The great challenge of the twentieth century was to bring knowledge to everyone, easy reading and knowledge as tools, training and another way of living. The XXI century has other commitments, including those recognized by most institutions, the quality of education. This requires improving outcomes, undergo external evaluations and especially apply and use new technologies that teachers and students and manage in real life. Educate to make better people, but also to help build a more just, stable and equitable society. They therefore offer some guidelines on education, quality on the models over a decade will be established in educational levels, as well as some programs already in place with interesting results. Apply some of these programs to the library, information and documentation.